Pain‐related unscheduled contact with healthcare services after outpatient surgery. (10th April 2017) - Brix, L. D.; Bjørnholdt, K. T.; Thillemann, T. M.; Nikolajsen, L.
Summary: This prospective, observational study explored the need for pain‐related unscheduled contact with healthcare services after outpatient surgery. We hypothesised that 10% of outpatients would have pain‐related unscheduled contact with healthcare services, and that the incidence would differ depending on the type of surgical procedure. In total, 905 patients who had undergone one of five common outpatient surgical procedures (knee or shoulder arthroscopy, surgical correction of hallux valgus, laparoscopic cholecystectomy or laparoscopic gynaecological procedures) completed an electronic questionnaire one week and eight weeks after surgery. Data from 732 patients (81%) were available for analysis. Within the first eight weeks after surgery, 150 patients (20.5%) had made unscheduled contact with healthcare professionals, in 247 cases due to pain that was most frequent in the first postoperative week. Risk factors were female sex, unemployment and laparoscopic cholecystectomy. The most frequent healthcare contact was with the general practitioner (46.4%), and the most frequent outcome was further information and guidance (41.2%). We have demonstrated that a minority of patients still needed to make contact with health services after outpatient surgery, most often due to inadequate pain management. This finding should be considered when planning postoperative monitoring and care, and developing postoperative patient education.